The study of relationship between biliary pathology and lipid-phospholipid changes in patients with non-alcoholic fatty liver disease and obesity - Філіппова, Олександра Юріївна (ScienceRise: Medical Science, 2016)
The aim of the work: The study of lipid-phospholipid indices depending on different pathology of biliary tract (BT) in patients with comorbid course of non-alcoholic fatty liver disease (NAFLD) in combination with obesity. Methods of research: There were examined 112 patients with NAFLD in combination with obesity and BT pathology: 60 patients with non-alcoholic hepatic steatosis (NAHS), 52 – with non-alcoholic steatohepatitis (NASH). Control group – 20 practically healthy persons (PHP). Depending on BT pathology patients with NAHS (n=60) and NASH (n=52) were divided into three subgroups: NAHS (1a group) or NASH (2a group) with chronic non-calculous cholecystitis (CNC); NAHS (1b group) or NASH (2b group) with chronic calculous cholecystitis (CCC); NAHS (1c group) or NASH (2c group) in patients with postcholecystectomical syndrome (PCES). The qualitative composition and quantitative content of lipids and phospholipids (PL) in the bloods serum were studied. Results: The least lipids changes were detected in patients with concomitant PCES comparing with groups of CNC and CCC. The data were proved by disperse and correlative analysis of connection between PL and BT pathology: at NAHS– рF=0,004; rs=0,306 (p<0,05); at NASH – рF=0,026; rs=0,279 (p<0,05). CNC and CCC led to the more increase of triglycerides level that PCES. According to the data of correlative analysis in groups of patients with NAHS and NASH was demonstrated that CNC and CCC led to the more essential decrease of sphingomyelin (SPM) level than PCES: at NAHS– rs=0,282 (p<0,05); at NASH –rs=0,317 (p<0,05). Conclusions. BT pathology influences the indices of spectrum of lipids and PL of the blood serum, first of all, PL, TG, SPM level at the different clinical forms of NAFLD in combination with obesity